Development of Integrated Writing Materials Based on Multiliteracies and High-Order Thinking Skills - Adiredja, Rajji K.; Hartati, Tatat; Riyana, Cepi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aimed to develop Integrated Writing Materials Based on High-Order Thinking Skills and Multiliteracies. This research utilized the D&D research method with the ADDIE design (Analysis, Design, Develop, Implementation, Evaluation). The subjects in this study are Elementary Schools located in the Garut regency. The instruments in this study include expert validation questionnaires, teacher and student response questionnaires, and test instruments to assess high-order thinking skills. Data analysis is conducted using a mixed methods approach. The results of developing multiliteracy-based teaching materials and high-level thinking skills obtained a good category from expert validation, teacher responses, and student responses. Subsequently, the teaching material developed in this research was piloted to students to assess its effectiveness on students’ high-order thinking skills. The results of the high-order thinking skills test after using the developed teaching material show that the average N-gain score at school 1 is 78%, which falls into the highly effective category. The average N-gain score at school 2 is 79%, also classified as highly effective. Lastly, the average N-gain score at school 3 is 81%, once again falling into the highly effective category. From these results, it can be concluded that the development of multiliteracy-based teaching materials effectively enhances students’ higher-order thinking abilities.